Qana'ah as the Spirit of Islamic Economics in Realizing Sustainable Agricultural Practices in Dua Boccoe District - Tri Putri, Afriliya; Syaparuddin Razak; Ismail Keri (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This research is motivated by the need for a spiritual approach to addressing the ecological crisis caused by chemical-based agriculture. The Islamic value of qana’ah, reflecting simplicity and sufficiency, is believed to be able to drive behavioral changes in farmers toward sustainable organic farming practices. The purpose of this study is to analyze the mediating role of qana’ah in the relationship between social norms and access to information, as influenced by technological innovation, on organic farming practices. The study used a quantitative approach using the SEM-PLS technique with 155 farmers in Dua Boccoe District, Bone Regency. The results indicate that qana’ah significantly mediates the influence of social norms and access to information on organic farming practices. Furthermore, technological innovation has an indirect effect on farming practices through improving social norms and access to information. In conclusion, qana’ah has proven to be a strategic value that integrates spiritual, social, and informational aspects in supporting ecological transformation in the agricultural sector. This study recommends the integration of qana’ah values into community-based sustainable agricultural education and policies.